2013
DOI: 10.1093/icvts/ivt442
|View full text |Cite
|
Sign up to set email alerts
|

Elastofibroma dorsi management and outcomes: review of 16 cases

Abstract: Elastofibroma dorsi is a rare, ill-defined, pseudotumoural lesion of the soft tissues. Surgical treatment can be proposed if the lesion is symptomatic. Furthermore, at the follow-up, the possibility of new occurrences on the contralateral side should be kept in mind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
0
21
0
4
Order By: Relevance
“…Tamimi Mariño et al 16 reported 10% recurrence rate after a mean post-surgical period of 47 months. Karakurt et al 11 observed no recurrences in their 16 patient series. In our patient, we totally excised the masses by bilateral subscapular incision.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Tamimi Mariño et al 16 reported 10% recurrence rate after a mean post-surgical period of 47 months. Karakurt et al 11 observed no recurrences in their 16 patient series. In our patient, we totally excised the masses by bilateral subscapular incision.…”
Section: Discussionmentioning
confidence: 83%
“… 8–10 Perhaps, multiple factors might account for the etiopathogenesis. Karakurt et al 11 reported 16 case with EFD. In this study 6 patients were manual laborers.…”
Section: Discussionmentioning
confidence: 99%
“…1 While recent developments in genetic analysis methods have provided new findings about the genomic changes in the pathogenesis of EFD, the data fall short of demonstrating that EFD is an outcome of chromosomal anomaly. 7 The most widely accepted view in explaining the pathogenesis of EFD describes EFD as a reactive formation. According to the classic view proposed by Jarvi et al 4 , repetitive microtraumas in the subscapular region caused by the friction between the lower end of the scapula and the thoracic wall leads to reactive hyperproliferation of the fibroelastic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Etyopatogenezi kesin olarak bilinmemekle birlikte, subskapular bölgede yineleyen mikrotravmalar sonrasında skapula alt ucunun göğüs duvarına sürtün-mesi sonucunda gelişen reaktif bir lezyon olabileceği düşünülmektedir. Yoğun kol performansı gerektiren sıklıkla ağır işlerde çalışan kişilerde ve baskın tarafta görülmesi, ED gelişiminde travmanın rolünün olabileceğini, hatta mesleki nedenlerin de etkili olabileceğini düşündürmüştür.…”
Section: Discussionunclassified